2019
DOI: 10.7717/peerj.7351
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of paddy soil quality under land consolidation: a novel perspective of microbiology

Abstract: Soil quality assessment is an important means to demonstrate how effective land consolidation is. However, the existing assessment system is not sufficient to reflect actual soil quality. So, the purpose of this study is to integrate abiological and biological indicators into a comprehensive assessment to evaluate the paddy soil quality under different land consolidation practices. Soil samples were collected from 35 paddy sites under different land consolidation practices including land merging, land leveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…One relevant study suggested that bacteria and fungi in soils generally account for more than 90% of all the soil microbial population [23], and some organic matter conversion processes in soils are controlled by soil microbial communities [24][25][26]. Soil microbial diversity can be used as an index for evaluating soil quality [26,27] and can be considered an important indicator for assessing soil stability under various environmental influences [28]. One reason is that diverse crop rotations affect the diversity and structure of the soil microbial community through root exudates, plant residues and symbiotic relationships [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…One relevant study suggested that bacteria and fungi in soils generally account for more than 90% of all the soil microbial population [23], and some organic matter conversion processes in soils are controlled by soil microbial communities [24][25][26]. Soil microbial diversity can be used as an index for evaluating soil quality [26,27] and can be considered an important indicator for assessing soil stability under various environmental influences [28]. One reason is that diverse crop rotations affect the diversity and structure of the soil microbial community through root exudates, plant residues and symbiotic relationships [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Under the current situation, it is possible to improve soil quality and increase the productivity of cultivated land by adopting appropriate farmland consolidation methods [ 30 , 31 ]. On this basis, we call to scientifically assess the impact of farmland consolidation on the structure of soil microbial communities, and extract microbial indicators of farmland quality [ 32 , 33 ]. This will be an important topic in the field of global farmland consolidation and ecological environmental protection in farmlands.…”
Section: Introductionmentioning
confidence: 99%
“…By establishing the minimum data set (MDS), we can easily select the most appropriate indicator to evaluate soil quality, and this indicator has been used widely [4,25,26]. The selection of MDS indictors can reduce the redundancy of soil data.…”
Section: Introductionmentioning
confidence: 99%